2014
DOI: 10.1007/s11033-014-3633-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a Δ5-like fatty acyl desaturase and its expression during early embryogenesis in the noble scallop Chlamys nobilis Reeve

Abstract: Long-chain polyunsaturated fatty acids (LC-PUFAs) are essential in lots of important physiological processes, while, many marine species have no or limited ability of endogenous PUFA biosynthesis, normally due to the lack of key enzymes such as fatty acid desaturase (FAD). In this study, we isolated a scallop Chlamys nobilis cDNA with high homology to vertebrate FADs. Functional characterization in recombinant yeast Saccharomyces cerevisiae showed that scallop FAD exhibited Δ5-desaturation activity towards bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 36 publications
8
41
0
Order By: Relevance
“…4−9 Contrarily, study on conversion rate of four scallop PUFA biosynthesis genes/enzymes reveals that scallop Elovl2/5, 26 Elovl4, and Fads2 tended to be more active toward n−6 substrates than n−3 substrates ( Figure 5D,E,I,J); only Δ5 Fad1 shows similar activity toward n−3 and n−6 substrates. 25 Similar results have also been reported in the common octopus, whose elongase has more activity toward n−6 FA substrates, 22 while Δ5 Fad shows equal activity toward n−3 and n−6 FA substrates. 21 The marine ecosystem is characterized by high levels of n−3 LC-PUFA, particularly EPA and DHA, 37 produced by marine microalgae, which then are passed on to high trophic mollusks through the food chain.…”
Section: ■ Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…4−9 Contrarily, study on conversion rate of four scallop PUFA biosynthesis genes/enzymes reveals that scallop Elovl2/5, 26 Elovl4, and Fads2 tended to be more active toward n−6 substrates than n−3 substrates ( Figure 5D,E,I,J); only Δ5 Fad1 shows similar activity toward n−3 and n−6 substrates. 25 Similar results have also been reported in the common octopus, whose elongase has more activity toward n−6 FA substrates, 22 while Δ5 Fad shows equal activity toward n−3 and n−6 FA substrates. 21 The marine ecosystem is characterized by high levels of n−3 LC-PUFA, particularly EPA and DHA, 37 produced by marine microalgae, which then are passed on to high trophic mollusks through the food chain.…”
Section: ■ Discussionsupporting
confidence: 78%
“…26 Further, a desaturase with Δ5 activity has been recently reported to desaturate 20:3n−6 and 20:4n−3 to AA and EPA. 25 In this study, a second Fad (Fads2) was cloned and functionally characterized to display Δ8 activity, providing the first compelling evidence that marine mollusks could at least de novo biosynthesize EPA and AA via the alternative "Δ8 pathway" of elongation−Δ8-desaturation−Δ5-desaturation. Consistent with the PUFA biosynthesis pathway observed in vitro, the FA profiles of scallop tissues indicated the existence of the alternative pathway accounting for the production of intermediates FAs 20:2n−6 and 20:3n−3 ( Table 3).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Chlamys nobilis (Liu et al, 2013(Liu et al, , 2014a, have confirmed similar substrate specificities to those described for the O. vulgaris genes, it remained unclear if the functions of A C C E P T E D M A N U S C R I P T …”
mentioning
confidence: 58%
“…Fad (Monroig et al, 2012a), 60.2 % identical to bivalve C. nobilis Fad (Liu et al, 2014a) and 53.6-65.8 % identical to homologues form the gastropods Lottia gigantea and H. discus hannai (Li et al, 2012). Lower identities (< 52.0 %) were observed when the cuttlefish Fad was compared with vertebrate (mammals and fish) front-end desaturases (Fads).…”
Section: S Officinalis Fad and Elovl Sequences And Phylogeneticsmentioning
confidence: 99%
“…Pioneer studies conducted in the common octopus Octopus vulgaris [10,11] and thereafter in the cephalopod Sepia officinalis [12], the gastropod Haliotis discus hannai [13] and the bivalve Chlamys nobilis [1416] have confirmed that molluscs and potentially other marine invertebrates possess Fads and Elovl enzymes involved in the LC-PUFA biosynthesis. Additionally, the ability to synthesise non-methylene interrupted (NMI) FA, a group of PUFA with particular double bond distribution [17], was observed in several Fads enzymes from marine invertebrate species [10,12].…”
Section: Introductionmentioning
confidence: 99%